2005
DOI: 10.1152/physiolgenomics.00173.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interaction between T cell-mediated β-cell damage and β-cell repair in the run up to autoimmune diabetes of the NOD mouse

Abstract: . Dynamic interaction between T cell-mediated ␤-cell damage and ␤-cell repair in the run up to autoimmune diabetes of the NOD mouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 71 publications
(61 reference statements)
3
66
0
2
Order By: Relevance
“…This result demonstrates TNF has significant effects on both CD4 + and CD8 + T cells. In NOD islets, TNF gene expression has been reported to peak at or before the onset of diabetes (48)(49)(50). We hypothesize that increased TNF expression in mice deleteriously effects regulatory T cell number and function and the deficiency in TNFR1 on regulatory T cells prevents this effect.…”
Section: Discussionmentioning
confidence: 90%
“…This result demonstrates TNF has significant effects on both CD4 + and CD8 + T cells. In NOD islets, TNF gene expression has been reported to peak at or before the onset of diabetes (48)(49)(50). We hypothesize that increased TNF expression in mice deleteriously effects regulatory T cell number and function and the deficiency in TNFR1 on regulatory T cells prevents this effect.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, other studies have emphasized the role of IL-17 in diabetes development in NOD mice. For example, it was shown that IL-17 transcripts increased during the evolution of diabetes in NOD mice (11) and that Th17 lymphocytes are activated in type 1 diabetic mice (15). Interestingly, in multiple low dose streptozotocin-induced diabetic mice, another murine model of type 1 diabetes, streptozotocin-stimulated IL-17 secretion promoted nitric oxidedependent toxic inflammatory responses toward MIN6, a mouse insulinoma cell line (10).…”
Section: Discussionmentioning
confidence: 99%
“…Komiyama et al (8) reported that IL-17 deficiency did not affect hyperglycemia in NOD mice, whereas other studies have emphasized the role of IL-17 in diabetes development (9 -14). For example, IL-17 mRNA was increased during the development of diabetes in NOD mice (11), and Th17 lymphocytes were activated in type 1 diabetic mice (15). Interestingly, the use of glutamic acid decarboxylase-derived peptide 206 -220-specific approaches to treat type 1 diabetes in NOD mice revealed that adjuvant-free antigens induced IFN␥ and controlled blood glucose via concomitant suppression of IL-17 secretion (9).…”
mentioning
confidence: 99%
“…Although the role of IL-17-producing cells in the development of diabetes has not been definitively addressed, it has been suggested that these cells may contribute to the pathogenicity of autoreactive T cells in the disease (19,20). The recently elucidated role for IL-21 in the development of Th17 cells (6-8) therefore suggested that Th17 cells might play a role in the IL-21-mediated development of diabetes, and increased IL-17 levels have been identified in the later phase of progression from insulitis to active diabetes (21). We investigated the development of Th17 cells in the prediabetic stage in NOD/WT and NOD/Il21r-KO mice.…”
Section: Normal T Cell Populations and Cytokine Production In Nod/il2mentioning
confidence: 99%